Participación de los padres de familia y hábitos de estudio en estudiantes de la Institución Educativa N° 60087 Lucille Gagne Pellerin, Santa Clotilde 2022 - Lachuma Garcia, Jenny (2024)
The objective worked was: Determine the degree of relationship between PPFF Participation and Study Habits in students of Educational Institution n°60087- Lucille Gagne Pellerín” Santa Clotilde 2022. The Independent variable: Participation of the Family Parent Participation (PPFF), is conceptually defined as: “involvement of parents in the school in a collaborative way (Castro-Zubizarreta & García-Ruiz, 2013).” Page 195 cited by (CastroZubizarreta & García-Ruiz, 2016) The Dependent variable: Study Habits, is conceptually defined as: “activities ordered to learn” (Negrete, 2009) The study was of a correlational type since it sought correlation between the variables, with a non-experimental design, and the data of the variables was collected at a specific moment and at a single time. The population is 103 students. The sample will be made up of 100% of the population selected for convenience. Through the interrelation of the V.I. (Parent participation) and the V.D. (Study habits), with the cross table Level of Parental Participation by Level of study habits, a result was obtained; regular with 57.3% and 60.2% respectively. In addition, the statistic - symmetrical measures - of Tau - b was used: the values indicate that it is a negative association (-.767), between the variables: “Parent Participation and Study Habits”. Basic statistics were also used, of which the results indicate that there is a low level of relationship between parental participation and study habits in students of educational institution N°60087- Lucille Gagne Pellerín” Santa Clotilde 2022. For the inferential analysis, the Kolmogorov-Smirnov method was used. (The normality test) The data fit a normal distribution and it can be concluded that the data is normal. To determine the correlations, Pearson correlations were used. It is determined that there is a positive correlation between both variables